The Influence of Typical Forest Types on Soil Erosion Resistance in the Water Source Areas of Central Yunnan - Zhao, Yangyi; Duan, Xu; Shu, Shumiao (Asian agricultural research, 2015)
In order to clarify the influence of different forest types on soil erosion resistance in water source area of Central Yunnan,with the soils under three different kinds of typical forest in Yizhe watershed as the research object,this paper uses field simulation method and principal component analysis to analyze the soil erosion resistance of three kinds of soils. The results show that there is a significant difference in the shear strength of soil among three types of typical forest,and the size of soil shear strength is in the order of Pinus yunnanensis forest land >mixed broadleaf-conifer forest land > eucalyptus forest land. The difference in the soil erosion coefficient among different forests is not significant,and the soil erosion resistance is highest in mixed broadleaf-conifer forest land( 39. 0%),followed by eucalyptus woodland( 37. 0%)and Pinus yunnanensis forest land( 24. 0%). Under heavy rain intensity and long duration of rainfall,the ability of soil under eucalyptus ×Pinus yunnanensis mixed forests to resist disintegration is more obvious. Using principal component analysis to analyze soil erosion resistance of soils under three different forests,we get the comprehensive evaluation model for soil erosion resistance: Y = 0. 763Y1+ 0. 236Y2. The soil erosion resistance is in the order of mixed broadleaf-conifer forest land( 0. 150) > eucalyptus forest land( 0. 127) > Pinus yunnanensis forest land(-0. 079),indicating that the mixed forests have better water loss and soil erosion control effect than pure forests.